3‐Year follow‐up of temporary implantable nitinol device implantation for the treatment of benign prostatic obstruction. (14th February 2018) - Porpiglia, Francesco; Fiori, Cristian; Bertolo, Riccardo; Giordano, Andrea; Checcucci, Enrico; Garrou, Diletta; Cattaneo, Giovanni; De Luca, Stefano; Amparore, Daniele
Abstract : Objectives: To report 3‐year follow‐up results of the first implantations with a temporary implantable nitinol device (TIND ® ; Medi‐Tate Ltd., Or Akiva, Israel) for the treatment of lower urinary tract symptoms (LUTS) secondary to benign prostatic hyperplasia (BPH). Patients and Methods: In all, 32 patients with LUTS were enrolled in this prospective study. The study was approved by the local Ethics Committee. Inclusion criteria were: age >50 years, International Prostate Symptom Score (IPSS) ≥10, peak urinary flow ( Q max ) <12 mL/s, and prostate volume <60 mL. The TIND was implanted within the bladder neck and the prostatic urethra under light sedation, and removed 5 days later in an outpatient setting. Demographics, perioperative results, complications (according to Clavien–Dindo classification), functional results, and quality of life (QoL) were evaluated. Follow‐up assessments were made at 3 and 6 weeks, and 3, 6, 12, 24 and 36 months after the implantation. The Student's t ‐test, one‐way analysis of variance and Kruskal–Wallis tests were used for statistical analyses. Results: At baseline, the mean (standard deviation, sd ) patient age was 69.4 (8.2) years, prostate volume was 29.5 (7.4) mL, and Q max was 7.6 (2.2) mL/s. The median (interquartile range, IQR) IPSS was 19 (14–23) and the QoL score was 3 (3–4). All the implantations were successful, with a mean total operative time of 5.8 min. No intraoperative complications were recorded. The change from baseline in IPSS, QoL score and Q max was significant at every follow‐up time point. After 36 months of follow‐up, a 41% rise in Q max was achieved (mean 10.1 mL/s), the median (IQR) IPSS was 12 (6–24) and the IPSS QoL was 2 (1–4). Four early complications (12.5%) were recorded, including one case of urinary retention (3.1%), one case of transient incontinence due to device displacement (3.1%), and two cases of infection (6.2%). No further complications were recorded during the 36‐month follow‐up. Conclusions: The extended follow‐up period corroborated our previous findings and suggests that TIND implantation is safe, effective and well‐tolerated, for at least 36 months after treatment.